Loanwords and Vocabulary Size Test Scores: A Case of Different Estimates for Different L1 Learners. Issue 3 (2nd July 2016) - Laufer, Batia; McLean, Stuart
ABSTRACT: The article investigated how the inclusion of loanwords in vocabulary size tests affected the test scores of two L1 groups of EFL learners: Hebrew and Japanese. New BNC- and COCA-based vocabulary size tests were constructed in three modalities: word form recall, word form recognition, and word meaning recall. Depending on the test modality, the tests measured the knowledge of 8, 000 lemmas or word families through 80 randomly sampled items, 6 of which were loanwords in Hebrew and 13 in Japanese. Therefore, we added the same number of non-loanwords from corresponding frequencies and performed within-subject comparisons between the scores of the original tests with loanwords and their non-loanword versions in which non-loanwords replaced loanwords. The comparisons were done for each L1 group, at each test modality, and at three L2 proficiency levels, as defined by the total non-loanword test score. We also compared the two L1 groups on the degree of loanword effect. In both L1 groups, tests with loanwords yielded significantly higher scores in all test modalities and among most proficiency groups. Less able participants gained more from the presence of loanwords. However, loanwords differently influenced the size estimates of the two L1 groups. Implications are suggested for creating vocabulary size tests and making inferences from vocabulary test data.